The Auvergne through the eyes of a Parisian or a tribute to the author's native country - Voždová, Marie (Romanica Olomucensia, 2016)
The article focuses on the analysis of opposite motifs, the countryside and the city, in a prosaic universe, particularly in the novel Les Pays by Marie Hélène Lafon, a contemporary French writer, a native of the Auvergne and living in Paris, whose works contain autobiographical elements. In her fiction, the author constantly mixes two spatiotemporal levels: the turbulent life of the capital city is confronted with the peaceful existence of a farm in the mountains. The interest is concentrated on the principal figure, Claire, who has to choose between the two worlds and live her life.
Keywords: contemporary novel; Lafon; Cantal; father; city; countryside.